Market orientation and performance: The interaction effect of entrepreneurial orientation - Jawad Hussain; Wali Rahman; Fayaz Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The centrality of resource-based view (RBV) from different angles and in diverse situations has widely been acknowledged, explored and researched. Keeping in view that the area still needs researchers' attention. This study looks into the possible impact of market orientation (MO) on organizational performance. The study will also be looking at the moderating role of entrepreneurial orientation (EO) in the MO and organizational performance link among the small and medium enterprises (SMEs). This is a survey type of qualitative and questionnaire based research. Sample size of the study is 213. The results of the study reveal the presence of positive relationship among the MO and organizational performance. The results of the study also demonstrate that the effects of MO on organizational performance are positively moderated by EO behaviors. This study covers the limitation of the previous studies by utilizing EO as a five-dimensional construct. This research fills the gap by probing the association of MO with organizational performance moderated by EO in a developing economy's context like Pakistan. This is an empirical study with a reasonable sample size and the results have both academic as well as practical implications. The study has a number of limitations like using a single informant for data collection and studying only one city. Future research directions have also been provided.
Keywords: 330